Performance Appraisal and Employee Commitment in Abia State Civil Service: A Focus on Ministries of Education and Works - Uchenna, Onyemaechi; Agu, Agu Godswill; Uche, Emmanuel Uche (Archives of Business Research, 2018)
This work focused on performance appraisal and employee commitment in Abia State Civil Service. The dynamic nature of employees’ commitment to their Ministries made this investigation very necessary. The objectives of the study were; to find out whether objective evaluation of employee performance has a positive relationship with employee affective commitment, to ascertain whether subjective evaluation of employee performance has relationship with employee continuance commitment. To achieve this objective, a survey research design was adopted. The techniques employed in analyzing the data were descriptive statistics and Pearson Correlation Coefficient. The results indicated that objective evaluation of employee performance has positive relationship with employee affective commitment. It was also found that subjective evaluation of employee performance has a weak and in significant relationship with employee continuance commitment. The study concluded that objective evaluation of employee performance has a positive relationship with employee affective commitment and subjective evaluation of employee performance has a weak relationship with employee continuance commitment in Ministries of Education and Works Umuahia. It was recommended that Directors/managers of public sector should ensure that performance criteria are clearly spelt against which employees at any level of management is appraised to ensure objectivity in the assessment.